The influence of principal transformational leadership and achievement motivation on teacher professionality - Novaliawati, Intan Rikha; Sulastri, Sulastri; Nellitawati, Nellitawati; Sabandi, Ahmad (Universitas Jambi, Indonesia, 2026)
This study examined the influence of principals’ transformational leadership and teachers’ achievement motivation on teacher professionalism in public senior high schools in Dharmasraya Regency. A quantitative survey design was employed. The sample consisted of 110 teachers selected through stratified proportional random sampling based on educational level and length of service. Data were collected using questionnaires that had been tested for validity and reliability. Multiple linear regression analysis was used to examine the individual and combined contributions of the independent variables to teacher professionalism. The results showed that principals’ transformational leadership accounted for 8.5% of teacher professionalism, while achievement motivation accounted for 37.7%. Together, principals’ transformational leadership and achievement motivation explained 38.1% of the variance in teacher professionalism. These findings indicate that both variables significantly contribute to teacher professionalism, although achievement motivation has a stronger contribution than transformational leadership. The study highlights the importance of strengthening school leadership practices and encouraging teachers’ achievement motivation to support professional development.